Pelatihan Microsoft Word pada Siswa dan Siswi di SMA Negeri 1 Tapung Hulu - Anjani, Sri; Megawati (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
This community service activity is carried out as a form of implementation of information system student practical work. Based on observations that have been made at SMA Negeri 1 Tapung Hulu, in general students of SMA Negeri 1 Tapung Hulu are familiar with computers, but knowledge in using Microsoft Word is still very minimal and there are still many students who do not understand the functions and uses of Microsoft Word itself. This happens because there is no computer extracurricular because of the lack of manpower and environmental conditions that do not allow. Through community service carried out at SMA Negeri 1 Tapung Hulu, it aims to help teach students about running a computer, especially for learning the basics of Microsoft Word. This training is expected to make it easier for students to do word processing in Microsoft Word. The method used in an effort to achieve the targets or goals that have been planned is the training method. The results of the implementation of this activity were that almost all of the training participants understood the material that had been presented, with the results of a questionnaire in the form of a questionnaire as much as 32% or 8 participants really understood the material provided during the training, 60% or 15 participants understood, and 8% or 2 participants lacked understand. Key words: Microsoft Word, Community Service, Training.